Neuroprotective Effects of Dexmedetomidine on the Ketamine-Induced Disruption of the Proliferation and Differentiation of Developing Neural Stem Cells in the Subventricular Zone - Sha, Huanhuan; Peng, Peipei; Wei, Guohua; Wang, Juan; Wu, Yuqing; Huang, He (Frontiers in Pediatrics, 2021)
Background: Ketamine disrupts the proliferation and differentiation of developing neural stem cells (NSCs). Therefore, the safe use of ketamine in pediatric anesthesia has been an issue of increasing concern among anesthesiologists and children’s parents. Dexmedetomidine (DEX) is widely used in sedation as an antianxiety agent and for analgesia. DEX has recently been shown to provide neuroprotection against anesthetic-induced neurotoxicity in the developing brain. The aim of this in vivo study was to investigate whether DEX exerted neuroprotective effects on the proliferation and differentiation of NSCs in the subventricular zone (SVZ) following neonatal ketamine exposure. Methods: Postnatal day 7 (PND-7) male Sprague-Dawley rats were equally divided into the following 5 groups: control group (n=8), ketamine group (n=8), 1 μg/kg DEX+ketamine group (n=8), 5 μg/kg DEX+ketamine group (n=8) and 10 μg/kg DEX+ketamine group (n=8). Immediately after treatment, rats received a single intraperitoneal injection of BrdU, and the proliferation and differentiation of NSCs in the SVZ were assessed using immunostaining at 24 h after the BrdU injection. In the olfactory behavioral tests, rats in each group were raised until 2 months old, and the buried food test and olfactory memory test were performed. Results: The proliferation of NSCs and astrocytic differentiation in the SVZ were significantly inhibited at 24 h after repeated ketamine exposure in the neonatal period, and neuronal differentiation was markedly increased. Furthermore, pretreatment with moderately high (5 μg/kg) or high doses (10 μg/kg) of DEX reversed ketamine-induced disturbances in the proliferation and differentiation of NSCs. In the behavior tests, repeated neonatal ketamine exposure induced olfactory cognitive dysfunction in the adult stage, and moderately high and high doses of DEX reversed the olfactory cognitive dysfunction induced by ketamine. Conclusions: Based on the present findings, pretreatment with a moderately high (5 μg/kg) or high dose (10 μg/kg) of DEX may alleviate the developmental neurogenesis disorder in the SVZ at 24 h after repeated ketamine exposure and improve olfactory cognitive dysfunction in adulthood.